Exploit your local resources - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
An organic farmer from Zambia, and an organic specialist with a crop buying agency discuss the benefits of organic methods for small scale farmers, particularly during times of food crisis.